Pemberdayaan Masyarakat Untuk Kewirausahaan Emping Melinjo Di Desa Wonokerso Kec. Limpung Kab. Batang Jawa Tengah - Imam Gozali; Asta Nugraha; Bambang Riyadi; Agung Wibowo (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
This service was held in Wonokerso Village, District. Limbung District. Stem. The aim is to empower the entrepreneurial community by non-working housewives. Techniques for implementing community service using learning and mentoring methods. The target of this service is 20 housewives. The results to be achieved are 1) the participants understand the meaning of creative entrepreneurship and are able to run a home business, especially making Emping Mlinjo. 2) Not only that, but also able to market their own products. Community Service as one of the Tri Dharma of Higher Education is carried out in a sustainable manner (sustainable)